2005
DOI: 10.1093/ajcn/81.1.50
|View full text |Cite
|
Sign up to set email alerts
|

n−3 Fatty acids consumed from fish and risk of atrial fibrillation or flutter: the Danish Diet, Cancer, and Health Study1–3

Abstract: Consumption of n-3 fatty acids from fish was not associated with a reduction in risk of atrial fibrillation or flutter. We cannot exclude the possibility of residual confounding caused by a lack of information on intake of fish-oil tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
2
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 15 publications
8
85
2
8
Order By: Relevance
“…On the other hand, studies found no associations between distinct ranges of portions/ frequency of fish consumption and any reduction in the risks of atrial fibrillation or arrhythmia (<2 times/week against 2 times/week) 28 , incidence of atrial fibrillation (~15g/day30 and 37 ~18g/day), of stroke (<1, 1-2 and >2 portions/week) 33 or of death by heart diseases (<0,5 to 2, 5 portions/ week) 26 . It must be highlighted that two 28,37 of these are among the five studies 7,28,35-37 on cardiovascular benefits with the largest samples investigated.…”
Section: Fish Consumption and Heart Diseasesmentioning
confidence: 94%
See 4 more Smart Citations
“…On the other hand, studies found no associations between distinct ranges of portions/ frequency of fish consumption and any reduction in the risks of atrial fibrillation or arrhythmia (<2 times/week against 2 times/week) 28 , incidence of atrial fibrillation (~15g/day30 and 37 ~18g/day), of stroke (<1, 1-2 and >2 portions/week) 33 or of death by heart diseases (<0,5 to 2, 5 portions/ week) 26 . It must be highlighted that two 28,37 of these are among the five studies 7,28,35-37 on cardiovascular benefits with the largest samples investigated.…”
Section: Fish Consumption and Heart Diseasesmentioning
confidence: 94%
“…Of the pathologies investigated, 13 studies assessed the association between fish consumption and cardiovascular diseases (ischemic heart disease, unspecified cardiovascular diseases, atherosclerosis progression, atrial fibrillation, arrhythmia, stroke, heart attack and venous thromboembolism) 6,7,9,10,13, 26,28,30,33,[35][36][37]39 ; 6 had analyzes on distinct types of cancer (not specified, prostate, breast, colon and renal cell) 15 , the linear trend 11 and the Person-time 16 were applied in a study each (Attached).…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations